Development of a Contextual QR-Based English Module to Enhance Elementary School Students' Critical Thinking Skills - Luki Bahari; Duwi Nuvitalia; Riris Setyo Sundari (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to develop and evaluate the feasibility and effectiveness of a contextual English module supported by QR codes to enhance fourth-grade students’ critical thinking skills. The research employed a Research and Development (R&D) method using the ADDIE model, involving 27 fourth-grade students from SDN 1 Jeketro, an urban public elementary school in Brebes, Central Java, as well as two external experts for content and media validation. Data were collected through expert validation sheets, classroom observations, and a critical thinking test using a one-group pretest–posttest design. The developed module demonstrated a high level of feasibility, achieving a mean validation score of 9.28 out of 10 from the content and media experts. Students’ performance improved substantially, increasing from 32.59% in the pretest to 70.74% in the posttest, with an N-gain score of 0.55, which falls into the moderate category. Among the assessed dimensions of critical thinking, analytical ability showed the most significant improvement, followed by evaluation and problem-solving skills. This pattern suggests that students became more capable of identifying relevant information, interpreting meaning, and drawing reasoned conclusions from contextual English materials. These findings indicate that a culturally contextualized QR code–based module is both feasible and effective in fostering critical thinking skills in primary English learning. The integration of local cultural content with structured digital support appears to create meaningful learning experiences that encourage deeper cognitive engagement. Furthermore, the results suggest that combining contextual pedagogy with accessible technology can strengthen not only language acquisition but also higher-order thinking processes. This approach offers practical implications for primary educators seeking instructional strategies that connect language learning with students’ lived experiences while promoting reflective and analytical thinking in a sustainable manner.